x + 2x - x + 7 = 4x - x + 2 Clean this up.
2x + 7 = 3x + 2
Subtract 2x from both sides.
7 = x + 2
Now subtract 2 from both sides.
5 = x ◄
Check
5 + 2(5) - 5 + 7 = 4(5) - 5 + 2
5 + 10 - 5 + 7 = 20 - 5 + 2
15 - 5 + 7 = 15 + 2
10 + 7 = 17 ■
4x + 2 + 2x - 2x = 14 4x = 14 - 2 4x = 12 x = 3
2x = 4x + 3 -2x = 3 x = -3 / 2
X equals 2 :)
(2x + 1)(2x + 1) or (2x + 1)2 so x = -0.5
If: 1-2x-5 = 4x+2 Then: -2x-4x = 2-1+5 And: -6x = 6 So: x = -1
4x + 2 + 2x - 2x = 14 4x = 14 - 2 4x = 12 x = 3
2x + 2 = 4x -1 2x = 3 x = 1.5
Simplify 4x + 3 = 2x + 8 2x = 5 x =2½
2x = 4x + 3 -2x = 3 x = -3 / 2
(2, 1)
X equals 2 :)
4x + 2 = 2x + 5 Subtract through by 2x 2x + 2 = 5 Subtract through by 2 2x = 3 Divide through by 2 x = 1.5 ■
(2x + 1)(2x + 1) or (2x + 1)2 so x = -0.5
If: 1-2x-5 = 4x+2 Then: -2x-4x = 2-1+5 And: -6x = 6 So: x = -1
2y = 4x + 4y = 2x + 2
-2x = -4x + 24 -2x + 4x = 24 2x = 24 x = 24/2 x = 12
4x + 5 = 2x + 19Subtract 5 from each side:4x = 2x + 14Subtract 2x from each side:2x = 14Divide each side by 2:x = 7